Economic growth, exchange rate and remittance nexus: Evidence from Africa - Adedoyin Isola Lawal; Afees A. Salisu; Abiola John Asaleye; Ezeikel Oseni; Bukola Bose Lawal-Adedoyin; Samuel Olatunde Dahunsi; Emmanuel Oluwasola Omoju; Abigail Oyeronke Dick Tonye; Elizabeth Bolatito Ogunwole; Abiola Babajide (Journal of Risk and Financial Management, 2022)
This paper examined the nexus between economic growth and exchange rate, remittances, trade, and agricultural output based on data sourced from 1980 to 2018 for 10 selected African economies. We employed both the Dumitrescu and Hurlin time-domain Granger causality test and the Croux and Reusens frequency domain Granger causality test. Results from the time-domain test suggests that causality only exists between economic growth and both exchange rate and trade, with no significant relationship between economic growth and both remittances and agricultural output. When we employed frequency domain model in our analysis, the results suggested that there is a bi-directional temporary and permanent causality between economic growth and exchange rate, trade, agriculture, and remittances. Our results suggest the validity of both the J-Curve and Marshall-Lerner hypotheses in the studied economies. Our study offers some relevant policy implications.
Keywords: 650; Africa; agricultural output; economic growth; exchange rate; remittances; trade